Outcomes of surgical treatment of patients with infratentorial metastatic tumors - Yuriy P. Zozulya; Volodymyr O. Fedirko; Viktor V. Gudkov; Dmytro V. Kubriak; Oleksandr M. Lisyanyi; Petro M. Onishchenko; Andrii G. Naboichenko; Tetyana M. Pushkaryova; Mariya Yu. Yakovenko (Ukrainian Neurosurgical Journal, 2018)
Objective. To determine the indications for surgical intervention and treatment tactic for metastatic infratentorial tumors.Materials and methods. The study included 162 patients with metastatic tumors of the infratentorial location treated from 1995 to 2018. One hundred and two patients (79.7 %) underwent total removal along the perifocal zone of tumor growth, 9 (7 %) — subtotal removal and 8 (6.3 %) — partial removal. In 5 (3.9 %) patients tumor removal was combined with CSF-shunting; in 4 (3.1 %) cases, surgical assistance was limited to the installation of a CSF-shunt system.Results. The most frequent sources of metastasis to the posterior cranial fossa were lungs — 42 (32.8 %) patients, the mammary gland — 19 (14.8 %) and melanoma — 15 (11.7 %). A separate large group consisted of patients with unknown primary focus (32 patients, 25 %).Out of 43 patients with known catamnesis there were 37 (86 %) patients with solitary metastases and 6 (14 %) persons with multiple metastases (including supra-infratentorial). The average survival after surgery in patients with solitary metastases was 8.4 ± 1.5 months, with multiple (including sub-supratentorial) 5.1 ± 0.8 months. Survival more than 1 year was observed in 13 (30.2 %) patients (1 patient (2.3 %) with multiple metastases).Conclusions. Patients with infratentorial metastases as well as with multiple metastatic brain lesions should be considered for surgery even if KPS < 70, especially due to CSF obstruction. Posterior fossa decompression with CSF flow restoration leads to survival prolongation, patients condition improvement and affords for further radiotherapy, chemotherapy or radiosurgery.